Transcription factor-driven regulation of ILC1 and ILC3. Issue 7 (July 2022) - Schroeder, Jan-Hendrik; Howard, Jane K.; Lord, Graham M.
Abstract : Mammalian innate lymphoid cells (ILCs) have functional relevance under both homeostatic and disease settings, such as inflammatory bowel disease (IBD), particularly in the context of maintaining the integrity of mucosal surfaces. Early reports highlighted group 1 and 3 ILC regulatory transcription factors (TFs), T-box expressed in T cells (T-bet; Tbx21 ) and RAR-related orphan nuclear receptor γt (RORγt; Rorc ), as key regulators of ILC biology. Since then, other canonical TFs have been shown to have a role in the development and function of ILC subsets. In this review, we focus on recent insights into the balance between mature ILC1 and ILC3 based on these TFs and how they interact with other key cell-intrinsic molecular pathways. We outline how this TF interplay might be explored to identify novel candidate therapeutic avenues for human diseases. Highlights: ILCs have an important role in mammalian tissues, providing an early immune response and a regulatory function to modify the adaptive and epithelial immune response. Group 1 ILCs (ILC1) are heterogenous depending on the role of either T-bet or Hobit as TFs for maintenance. Group 3 ILC (ILC3) express several TFs that appear to inhibit their plasticity toward ILC1, and these include RORγt, RORα, c-Maf, and HIF1. By contrast, T-bet, in conjunction with Aiolos and Bcl6, promote ILC1. The balance between ILC3 and ILC1 appears to be crucial for the severity outcome of IBD, colorectal cancer, and likely other diseases.